Communication Styles of Single Parent for Gen Z in Kisaran - Sarah Bonova Bere Sinaga; Nurbani; Mazdalifah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze communication styles and communication barriers that occur between SIngle parent and Gen Z in the city of Kisaran. The informants in this research are SIngle parent who live in the city of Kisaran and have children from Gen Z. This research was conducted using a qualitative approach with descriptive methods. The theory used in this research is communication styles and barriers which were coined by J.A Waters and Joseph de Vito to analyze the process of communication styles and communication barriers that occur between SIngle parent and Gen Z children. The number of informants in this research to achieve saturated data is seven informants divided into two categories, five main informants and two triangulation informants. Data collection techniques were carried out using in-depth interviews and observation. The results of the research show that the communication style used by SIngle parent is an assertive communication style, parents are more active in communicating first and try to actively communicate with their children. Communication barriers that occur between SIngle parent and Gen Z children are physiological barriers, namely disturbances that occur in the communication process due to the physical or biological conditions of the individuals involved, such as visual disturbances from SIngle parent, and semantic barriers, disturbances that occur in the communication process due to differences. the meaning or interpretation of the words and symbols used such as language differences between parents and their children